Developing English and Information Technological Potential for Ornamental Fish Famers in Nakhon Pathom Province for Getting Ready to the Asean Economic Community (AEC) - Sukcharoenpong, Sompon; Chanasuk, Kasamol; Dithasathorncharoen, Santi; Wonginyu, Kanokphat (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This study aimed to develop English and information technological potential for the farmers who grow ornamental fish in Nakhon Pathom Province in order to get ready for ASEAN Economic Community (AEC). The participants were 30 farmers in Nakhon Pathom Province. All participants have been trained for developing their English and information technological potential for two weeks. This two-week training course totally took 70 hours which was divided into ten times, and each time took 7 hours. The results revealed that after attending the two-week training course, the skills of using English and information technology of the farmers who culture ornamental fish in Nakhon Pathom weresignificantly higher at 0.01. The mean scores of the potential tests of English and information skills provided before and after enrolling the two-week training were 37.72 and 49.61 respectively, calculated from the total score of 60. Article history : Accepted 7 July 2014 SIMILARITY INDEX = 0.00